PENGARUH DZIKIR TERHADAP PSIKOLGIS MUSLIM - Aliasan, Aliasan (Yonetim Jurnal, 2019)
Abstract: This article aims to explain the attitude will be formed in a person. Many factors can influence a person's mindset, maybe environmental factors or educational factors and experience factors. The problems in this questionnaire will be discussed through descriptive and qualitative library research. This means that the data sources in the completion of this paper both primary and secondary were obtained from various literatures and described qualitatively. There are two types of data analyzed in this single writing, namely data about dhikr and psychology, both of which will support each other and influence if both are in someone's self. The data analysis technique used is deduction, namely analyzing data from general to specific. The results of the analysis carried out are that Dhikr has psychological and spiritual benefits, psychologically, giving a sense of comfort and spiritually giving a feeling that is closer to God. In the inner peace of the individual who plays a fundamental role is the belief in religion based primarily on the statement of the Holy Qur'an. Dhikr can form a good person and avoid acts of immorality (sin), eliminate anxiety, dzikir also purifies the heart of all negative attitudes and emotions and so on, and most importantly that dzikir sangt affects the existence of the heart, aik is explained by the Quran and hadith and by previous studies. Keywords: Dhikr, Psychology